ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, PENGENDALIAN INTERNAL, DAN KUALITAS LAPORAN KEUANGAN (STUDI PADA SKPD BENER MERIAH) - Safrizal, Nanda; Fitri, Fauziah Aida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The financial statements are one of the most important and inseparable elements of an entity. The preparation of government financial statements is a manifestation of the transparency and accountability of state financial management. This research was conducted in 2017. The purpose of this study is to find how well the application of Government Accounting Standard, internal control, and quality of financial statements in SKPD Bener Meriah. Sources of data in this study gathered from the primary data. The data required in this study are data that is associated with the implementation of SAP, internal control, and quality of financial statements. These data are collected by using questionnaires that will be distributed to each respondent. The respondents in this study are head of SKPD, head of finance, and finance staff. The results concluded that the application of government accounting standards and internal controls can be stated that have been applied correctly in accordance with applicable government regulations. The quality of the financial statements in SKPD Bener Meriah also has good quality, it can be identify based on the opinion given by BPK.